2015 International Conference on Electrical Engineering and Informatics (ICEEI) 2015
DOI: 10.1109/iceei.2015.7352491
|View full text |Cite
|
Sign up to set email alerts
|

DGA and tensile strength test on accelerated thermal aging of ester oil and kraft paper

Abstract: This paper reports experimental results on chemical and mechanical properties of ester oil and kraft paper under accelerated thermal aging process. 800 ml of ester oil and 10 insulation kraft paper sheets were put together in heat-resistant bottles. All samples are conditioned to the same initial conditions through the heating at a temperature of 100 °C for 24 hours. The bottles containing oil and paper samples were then subjected to thermal aging process at 120 o C and 150 o C. Dissolved gas and tensile stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…The transformer insulation paper was wrapped around the copper metal strip. Firstly, the natural ester samples in the glass bottles were heated without sealing at a temperature of 100 • C for 24 h in order to ensure the same initial conditions [1,15,16]. Then the transformer insulation paper and copper metal strip were put into heat-resistant and sealed glass bottles.…”
Section: Introductionmentioning
confidence: 99%
“…The transformer insulation paper was wrapped around the copper metal strip. Firstly, the natural ester samples in the glass bottles were heated without sealing at a temperature of 100 • C for 24 h in order to ensure the same initial conditions [1,15,16]. Then the transformer insulation paper and copper metal strip were put into heat-resistant and sealed glass bottles.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis can be also utilised to describe the paper ageing through CO and CO 2 dissolved in the oil. Different works have showed that there is a relationship between the concentration of these gases and the DP (CO 2 /CO ≤ 7.4, DP > 600; 7.4 < CO 2 /CO < 8.0, 400 < DP < 600; 8 ≤ CO 2 /CO < 8.7, 250 < DP < 400; CO 2 /CO ≥ 8.7, DP < 250) [34,35]. The gases, which can be extracted from the oil using different methods [18], are detected using the gas chromatography technique whose operating principle is like HPLC.…”
Section: Dissolved Gas Analysismentioning
confidence: 99%
“…They found a slight variation of the tensile index in the three oils. The degradation of Kraft paper aged in a natural ester was also evaluated through the tensile strength by Widyanugraha et al [35], who also measured the gases generated during ageing at two different temperatures. The tensile strength suffered initially a decrease and subsequently an increase during thermal ageing.…”
Section: Accelerated Thermal Ageing In Laboratorymentioning
confidence: 99%
“…Additionally, these authors measured dissolved gas in dielectric oil. The failure rate of transformer insulation systems made up of Kraft paper and mineral oil and two different vegetal oils was evaluated by Madavan and Balaraman [23]. They aged the insulation systems at 140ºC and tested dielectric strength, acidity, dissipation factor, resistivity and tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several authors have modeled the relationship between the variation of the tensile strength and the degree of polymerisation (DP) over time [25][26]. Another more recent studies [21,[27][28][29][30] have correlated the variation of the tensile strength with properties of the oil such as: dissolved gases, furans content [28], breakdown voltage, acidity and water content [27,31].…”
Section: Introductionmentioning
confidence: 99%